Climate Futures Across Disciplines (Taylor & Francis, 2026)
Climate Futures Across Disciplines explores the multifaceted nature of climate futures, showcasing how early-career researchers are helping to pioneer what innovation in academia might look like. The volume shows how emerging scholars can sustain disciplinary rigour while engaging wider ecological, political, societal, and perceptual concerns. Instead of treating climate change purely as scientific or policy analysis, the book approaches future-oriented thinking as a domain of imagination, design, and governance. Initial chapters translate climate change into lived or felt experience through creative performance, visual practice, and palaeoclimate analogues, then move to infrastructure design, fair transport decarbonisation, renewable energy markets, and inclusive water governance. The final section considers governance, law, and institutional responsibility, illustrating how climate futures unfold in sanitation systems, mining towns, carbon markets, and environmental rights frameworks. Throughout, contributors emphasise that climate futures are lived, negotiated, and unevenly experienced. Their analyses foreground justice, lived experience, and practical insight, while recognising the need for future research that connects grounded practices to accelerating risks and inequalities. Breaking academic barriers to inspire new and innovative research approaches, this book will be of interest to students and scholars of social justice, environmental justice, climate justice, and human rights, as well as to policymakers, activists, NGOs, and public interest lawyers.